2004
DOI: 10.1177/073401680402900108
|View full text |Cite
|
Sign up to set email alerts
|

Community Member Reactions to Prison Siting: Perceptions of Prison Impact on Economic Factors

Abstract: Recent increases in prison populations and growth in prison construction have brought issues related to prison siting to the forefront. Although the NIMBY (Not In My Back Yard) syndrome is often discussed in literature pertaining to prisons and community development, relatively little empirical research has been devoted to this topic. Based on a survey of residents of a county in which construction of a new prison was just beginning, this article focuses on the perceived impact of the new prison on future prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 18 publications
0
14
1
Order By: Relevance
“…In contrast to studies that conclude that public transport and distance to local settlements are important in selecting the establishment's location (Carlson, 1992; Krause, 1992; Myers & Martin, 1994), ‘distance to the city center’ was an extremely insignificant factor in our study, with a weighting of only 1.8%. This may have been because penal institutions in Turkey are structured as campuses, complete with staff lodgings, schools, and shops.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to studies that conclude that public transport and distance to local settlements are important in selecting the establishment's location (Carlson, 1992; Krause, 1992; Myers & Martin, 1994), ‘distance to the city center’ was an extremely insignificant factor in our study, with a weighting of only 1.8%. This may have been because penal institutions in Turkey are structured as campuses, complete with staff lodgings, schools, and shops.…”
Section: Discussioncontrasting
confidence: 99%
“…The selection of the right prison location should lead to an active development process so as to eliminate opposition within the selected region by ensuring a net positive economic contribution. The distance from the establishment to public transport and settlement areas is another factor investigated in previous studies (Carlson, 1992; Krause, 1992; Myers & Martin, 1994). These studies have reported that the proximity of settlement to public transport is an important factor in choosing a prison's location.…”
Section: Introductionmentioning
confidence: 96%
“…Although individual states' incarceration rates continue to significantly vary from each other, ranging from a low of 128 in Minnesota and a high of 801 in Louisiana by year-end 2000, they all grew by roughly the same multiplier in the late 20th century (Beck & Harrison, 2001;Zimring & Hawkins, 1991). As a result of this dramatic growth in the prison population, states began building new facilities across the nation by the end of the 1970s, with the construction accelerating through the late 1980s and early 1990s at a rate unprecedented in history (Lawrence & Travis, 2004;Myers & Martin, 2004). The majority of the new construction has been in rural areas, with 350 new rural facilities opening in the last 2 decades of the 20th century (King, Mauer, & Huling, 2003).…”
Section: Prison Building As a Regionally Specified National Phenomenonmentioning
confidence: 99%
“…In many jurisdictions, the new wave of construction has been justified simply as a necessity to meet the dual demands of federal courts that required conditions comply with the Constitution, and state and local courts that sent rapidly increasing numbers of offenders to prison (Lynch, 2009;Schoenfeld, 2008). This has been followed, in a number of jurisdictions, by a trend in which state political actors have explicitly sold prison construction to local, generally rural, civic leaders and citizenry as an economic stimulus opportunity (Gilmore, 2007;Huling, 2002;Myers & Martin, 2004). Thus, the linkage between the criminality of individual offenders and the ''account'' of the institution's purpose has become somewhat decoupled, allowing the prison to more explicitly serve purposes outside of its basic custodial and corrective functions.…”
Section: Prison Building As a Regionally Specified National Phenomenonmentioning
confidence: 99%
“…As a consequence, many residents living near proposed or operational correctional facilities report that their behaviors or intended behaviors have been altered as a result of the facility placement. Recent investigations (Martin 2000; Martin and Myers 2005; Myers and Martin 2004) of community attitudes regarding effects of prison placement suggest that while worries about safety were not overwhelmingly voiced, concern about property values “yielded the highest rate of negative responses” (Martin 2000:286) and 8 percent of the sample indicated they wanted to move farther away from the prison or out of the county altogether. Similar sentiments were voiced in regard to a correctional halfway house in a northeastern town, with researchers finding that the majority of interviewed residents believed that property values had declined as a result of the correctional placement and many respondents were willing to sell their homes below market value (Kilburn et al 2014).…”
Section: Introductionmentioning
confidence: 99%